Cómo mejorar el posicionamiento de Colombia en las exportaciones de aceite de palma al Brasil - Bermúdez Jiménez, Daniela Fernanda; Moncada Sanchez, Mabel Stefany (Universidad Antonio Nariño, 2023)
According to data provided by Fedepalma, palm oil production Colombia is developed in practically all areas of the country, especially in the zone Oriental with approximately 42%. For its extraction, you must start from the cultivation of the Palm which, after two years, bears fruit which can reach 28 to 30 years of exploitation. Of the total national production, 64% is intended for local consumption and the remaining 36% for exports, with Brazil being one of the main destinations during the five-year period between 2014 and 2019. The international price of a ton of palm oil Colombian currency remained from USD 554.29 to USD 747.28, with reference to the production, costs, demand and national and international consumption.